What Is The Comparative Effectiveness Of Anti-VEGF Therapy Versus Laser Photocoagulation In Reducing Visual Impairment For Patients With Diabetic Macular Edema? : A Systematic Review - Mia Audina; Olivia Putri Chairunnisa; Irawati (The International Journal of Medical Science and Health Research, 2025)
Introduction: Diabetic macular edema (DME) is a leading cause of vision loss in working-age adults, driven by vascular endothelial growth factor (VEGF)-induced fluid accumulation. While laser photocoagulation was once the standard treatment, anti-VEGF therapies (e.g., ranibizumab, aflibercept, bevacizumab) have emerged as superior alternatives. This study compares the effectiveness of anti-VEGF therapy versus laser photocoagulation in improving visual and anatomical outcomes in DME patients. Methods: A systematic review was conducted following PRISMA 2020 guidelines, analyzing 40 studies (2016–2023), including 24 randomized controlled trials (RCTs). Inclusion criteria comprised adult DME patients, direct anti-VEGF vs. laser comparisons, and ≥6-month follow-up. Data were extracted on visual acuity (BCVA), central macular thickness (CMT), safety, and treatment frequency. Results: Anti-VEGF therapy significantly outperformed laser, with BCVA gains of +6.8 to +10.5 letters versus +1.1 to +1.4 letters for laser (Li et al., 2019; Heier et al., 2016). CMT reductions were greater with anti-VEGF (-123 µm to -313 µm) compared to laser (-85.9 µm). Early response (within 3 months) predicted sustained benefits, maintained for up to 5 years. Combination therapy (anti-VEGF + laser) reduced injection frequency by 20–40% without compromising efficacy. Safety profiles favored anti-VEGF, with rare serious ocular adverse events (<1%), while laser carried risks of peripheral vision loss. Discussion: Anti-VEGF therapy is the gold standard for DME, offering superior functional and anatomical outcomes. Combination strategies may reduce treatment burden, though protocols require standardization. Socioeconomic barriers to frequent injections remain understudied. Conclusion: Anti-VEGF agents are more effective than laser in treating DME, with sustained visual and anatomical benefits. Future research should focus on long-term outcomes, cost-effectiveness, and optimizing combination therapies.